Nós falaremos por nós : uma encruzilhada autoetnográfica sobre a construção da identidade negra a partir das comunidades tradicionais de terreiro - Santos, Erikson Bruno Mercenas (2022)
The present research, aims to identify through the writings the possible contributions of the Traditional Communities of Terreiro (CTTro) in the construction of the black identity against hegemonic from an autoethnographic research. The writings are black experiences that start from the collectivity as an instrument that registers a new consciousness and a new civilizational landmark, rethinking history from a perspective historically marginalized by colonization. There is talk of the lived place and the crossroads traveled (EVARISTO, 2008). It is important to point out that writing is the place for denunciations and productions of the unsaid discarded by hegemonic science (ANZALDÚA, 2000). The writings referring to the CTTro, demand a methodology outside the guidelines elaborated in the colonialities, they invite us to decolonize the plastered forms of academic methods. It is important to highlight that this work is located in the area of Applied Inter/Transdisciplinary Linguistics, which has as its assumptions a critical transgressivity focused on practices and social contexts and their problems, enabling a reconfiguration of the thinking and status quo of a new world through perspectives. non-westernized (PENNYCOOK, 2006), with the desire to dialogue with colonial pains, with the plastering of identity, affirming to the world that we live in new times, with diverse and non-homogeneous practices, and that complexity awakens a new look (MOITA LOPES, 2009). This research also starts from the possibilities of a Post-Colonial Critical Linguistics (MUNIZ, 2016), with which it is possible to understand the society in which we are inserted, being essential to stick to the relationship between identity, language and raciality, as these three concepts are inserted in the historical and structural context of the political project of colonization, thus, it is necessary to combine this discussion with a critical and political vision. Thinking about the black identity inserted in the CTTro from the place of ethnographer makes it possible to develop technologies against colonials to face history in a constructive way, issuing and problematizing messages, referencing epistemologies of terreiro and the voices inserted in marginalization to counter what is posed by colonization, leaving the pursuit of healing through the crossroads of Exú, in a black and transgressive ethics (RUFINO, 2019; NOGUEIRA, 2020). The methodology of an autoethnographic nature in this dissertation, makes it possible, from the traditional communities of terreiro, to occupy the place of those who have to talk and present, distancing themselves from the impressions of the white man, therefore, it becomes a way of denouncing a history made invisible in an imperialist science. In my view, terreiro experiences call for awareness of being black in their society masked by racial democracy, meritocracy and the secular rule of law. The terreiro is not limited to physical space, its dimension is philosophical, linguistic and cultural (SODRÉ, 2002).